Comparison of Optic Nerve Sheath Diameter (ONSD) Measurements Obtained from USG Before and After Placement of Ventriculoperitoneal Shunt in Obstructive Hydrocephalus as a Surrogate Marker for Adequacy of Shunt Function: A Prospective Observational Study - Salih, M. S. Mohamed; Sethuramachandran, Adinarayanan; Bidkar, Prasanna Udupi; Dey, Ankita; R., Gopikrishnan; Gunasekaran, Adethen; Chandar, Vivek (Asian Journal of Neurosurgery, 2024)
Introduction Optic nerve sheath diameter (ONSD) measured using ultrasonography has been widely used as a surrogate marker of elevated intracranial pressure. However, literature is sparse on the correlation between ONSD and ventriculoperitoneal (VP) shunt function, especially in adults with hydrocephalus. Our study was designed to assess the correlation between ONSD measured using ultrasonography before and 12 hours after VP shunt placement and the success of VP shunt placement assessed using computed tomography (CT) of the brain.Materials and Methods Fifty-one patients between 16 and 60 years of age, with obstructive hydrocephalus scheduled for VP shunt surgery were included in this prospective, observational study. ONSD measurements were obtained from both eyes prior to induction of anesthesia, immediately after the surgery, and at 6, 12, and 24 hours after the surgery. An average of three readings was obtained from each eye. Cerebrospinal fluid (CSF) opening pressure was noted after entry into the lateral ventricle. Noncontrast CT (NCCT) brain was obtained 12 hours after the surgery and was interpreted by the same neurosurgeon for signs of successful VP shunt placement.Results There was a significant reduction in ONSD in the postoperative period compared to ONSD measured preoperatively. The average ONSD (mean ± standard deviation) measured prior to induction of anesthesia, immediately after the surgery, and at 6, 12, and 24 hours after the surgery was 5.71 ± 0.95, 5.20 ± 0.84, 5.06 ± 0.79, 4.90 ± 0.79, and 4.76 ± 0.75 mm, respectively. The mean CSF opening pressure was 19.6 ± 6.9 mm Hg. Postoperative NCCT brain revealed misplacement of the shunt tip in only one patient.Conclusion ONSD measured using ultrasonography may be used as a reliable indicator of VP shunt function in adults with obstructive hydrocephalus.
Keywords: computed tomography scan; hydrocephalus; optic nerve; ultrasonography; ventriculoperitoneal shunt